Prevention of Thromboplastin-induced Thrombosis in Rabbits by Means of Plasmin - Storm, Ole (Thrombosis and Haemostasis, 1959)
1. By administration to rabbits of plasmin produced by activation of human plasminogen with human urine activator, fibrinolysis in the blood was obtained without observable side effects.2. A single injection of plasmin protects the animals from a fatal intra vascular coagulation produced by a subsequent thromboplastin administration. Among the control animals treated with inactive plasmin, ⅔ of the animals died from pulmonary thrombosis or massive intracardial coagulation of the blood.